Relationship Of Knowledge And Attitude With Behavior About Breast Care In Breastfeeding Mothers (At The Tempe Health Center, Wajo Regency) - Yusda Seman; Mukarrama; Irmawati (Jurnal Life Birth, 2023)
Background: Breast care is a treatment given to keep the breasts in good condition during breastfeeding, including breast hygiene before and after breastfeeding. Objective: To determine the relationship between knowledge and attitudes with behavior about breast care in breastfeeding mothers. Methods: This type of research uses a quantitative research design with a cross-sectional research method because, in this study, the independent and dependent variables will be observed at the same time (period), the population in this study is breastfeeding mothers in August 2022, the sampling technique is done by purposive sampling, obtained 30 respondents. Data was collected using a questionnaire sheet. The collected data was then processed and analyzed using a computer program, Microsoft Excel, and a statistical program (SPSS) and data analysis using the chi-square test. Results: Based on the analysis of the results of the Chi-Square test, the value of p = 0.02 (<p = 0.05), which means Ha is accepted and H0 is rejected, so it can be concluded that there is a relationship between attitudes and behavior about breast care in breastfeeding mothers at the Tempe Health Center, Wajo Regency. Conclusion: There is a relationship between knowledge and attitudes with behavior about breast care in nursing mothers at the Tempe Health Center, Wajo Regency. Suggestion: It is hoped that further research can be carried out with broader research.